DB or not DB: Writing the history of the slave trade to North America in the era of the database - Kelley, Sean M. (History compass, 2019)
Since the publication of the Transatlantic Slave Trade Database (now known as Voyages) in 1999, it has occupied an important place the study of the North American slave trade. Some historians, particularly those interested in the African Diaspora and African American culture, have embraced its ability to elucidate the specific connections between Africa and North America over time. While most historians have accepted the validity of the database, some have criticized the database's tendency to privilege quantitative abstraction over a more "human" narrative. A smaller number still have rejected the estimates offered by the database specifically regarding the number of Africans disembarked in the United States after 1808, but most scholars in the field have accepted the Voyages estimates. There are now plans to link the Voyages database with a number of other slavery-related digital history projects, which suggests that the era of the database is here to stay.